2019
DOI: 10.1007/s40368-019-00482-0
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of intravenous propofol sedation for adolescent dental care

Abstract: Purpose Propofol is an intravenous anaesthetic agent commonly utilised in general anaesthesia, however in sub-anaesthetic concentrations can be utilised to provide sedation through automated dosing of target-controlled infusion (TCI). TCI has been shown to provide accurate and stable predicted plasma and effect-site concentrations of propofol. A four-part mixedmethod prospective study was undertaken to evaluate the safety and patient acceptability of intravenous propofol sedation in adolescent patients requiri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 16 publications
0
9
1
Order By: Relevance
“…Ninety-five percent of the patients reported that this technique met their needs, and 99% were completely satisfied. The satisfaction rate reported in this study was higher than that reported by Dixon et al [ 35 ] and Pourabbas et al [ 36 ].…”
Section: Discussioncontrasting
confidence: 83%
“…Ninety-five percent of the patients reported that this technique met their needs, and 99% were completely satisfied. The satisfaction rate reported in this study was higher than that reported by Dixon et al [ 35 ] and Pourabbas et al [ 36 ].…”
Section: Discussioncontrasting
confidence: 83%
“…One of propofol's downsides, that is, the need for an expensive infusion pump, could be mitigated by administering it in this manner. [ 11 12 13 14 15 ] The conventional procedure for deep tranquility or general anesthesia in the course of oral and maxillofacial surgery is the intermittent bolus technique. Many investigations comparing intermittent bolus versus continuous infusion strategies reported no significant differences in adequate tranquility and diagnostic procedure quality.…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 ] Deep tranquility's superiority over general anesthesia is supported by its advantages, which include a shorter recovery time, less patient preparation, and less monitoring equipment and skill. [ 7 ] Chloral hydrate,[ 8 ] meperidine,[ 9 ] hydroxyzine,[ 10 ] promethazine,[ 11 ] ketamine,[ 12 ] propofol,[ 13 ] and midazolam[ 14 ] have all been utilized as sedative agents in the dental therapy of pediatric patients, and each has its own set of benefits along with drawbacks. Propofol is the most commonly utilized medicine in intravenous tranquility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Qualitative research is a powerful tool for exploring experience through student voice; it gives perspective and insight whilst protecting varying values, backgrounds and expectations 20,21 . Previous examination of CS education seldom employed qualitative research methods, as studies have been survey‐based, 6,9 or focussed on patients or qualified healthcare professionals 22‐27 . One useful qualitative research method is personal semi‐structured reflective logs 21,28,29 …”
Section: Introductionmentioning
confidence: 99%